Cloning and Characterization of 1,8-Cineole Synthase (SgCINS) Gene From the Leaves of Salvia guaranitica Plant - Ali, Mohammed; Alshehri, Dikhnah; Alkhaibari, Abeer Mousa; Elhalem, Naeema A.; Darwish, Doaa Bahaa Eldin (Frontiers in Plant Science, 2022)
Monoterpenes are one of the most common groups belonging to the terpenoid family, with a C10 structure comprising of two isoprene units. Most of monoterpenes are volatile plant compounds and they act as plant signaling between plants and the environment, particularly as defensive compounds against herbivores and pathogen. In this work, 1, 8-cineole synthase gene SgCINS was identified and cloned from leaves of Salvia guaranitica plant. To examine the role of SgCINS in insect resistance, we transformed and expressed this gene into tobacco leaves. Metabolic analysis revealed that the production of various types and amount of terpenoid were increased and decreased in SgCINS overexpression and control lines, respectively, suggesting that overexpressing SgCINS in transgenic tobacco plants lead to increased the production of various type of terpenoid and other phytochemical compounds. These results indicated why the transgenic tobacco was highly resistant to cotton worm than non-transgenic control that was highly susceptible. Our results demonstrate that SgCINS gene can plays an important role in plants against cotton worm insect attack, and paves the way for using terpenoids genes for improving resistance to insect attack in higher plants